Radiography Managers Perspectives on Radiographer Supply and Demand in KwaZulu-Natal Public Healthcare, South Africa - Cibane, Nonkululeko; Hoque, Muhammad (Diversity: Disease Preventive of Research Integrity, 2025)
The unbalanced distribution of Health Workers (HCWs) is a public health challenge. In South Africa, public sector radiography services are not meeting demand due to vacant positions, recruitment freezes, increased workloads, and low retention of radiographers, which negatively impacts quality and service delivery. This study aimed to explore radiography managers’ perceptions and views about supply and demand in relation to the radiographers working in the public healthcare sector of KwaZulu-Natal province (KZN). The exploratory qualitative study utilized semi-structured interviews with open-ended questions to acquire data. Ten radiography managers were purposefully selected from the 22 hospitals in the province of KZN. Thematic analysis was used to identify themes from the qualitative data using NVIVO Pro 12. The results showed that the decision-makers do not properly understand or value, the need for radiographers in the health environment. The lack of advocacy for and representation and engagement between the employing principals and radiographers leaves the sector understaffed and overworked. Disharmony between employers and radiographers, as well as unresponsive decisions, affect retention and recruitment. The oversupply and low uptake of qualified radiographers is due to delays in policy implementation, particularly recruitment and retention. Key gaps include professional advocacy in decision-making bodies, effective policy implementation with monitoring, improvement of the working environment, and development of radiographer career pathways.